Інноваційні підходи до організації оздоровчо-рекреаційних занять із дітьми дошкільного віку - Сухомлинов, Рудольф Олегович; Sukhomlynov, Rudolf (Східноєвропейський національний університет імені Лесі Українки, 2017)
Вивчено інноваційні підходи до організації рекреаційних занять із дітьми дошкільного віку на базі спортивно-оздоровчих клубів. Результати опитування дали змогу встановити, що батьки схвально ставляться та високо оцінюють інноваційні підходи до організації оздоровчо-рекреаційних занять на базі клубних об’єднань. Особливою атрактивністю серед дітей дошкільного віку користуються дитячі футбольні клуби. Інтерес до занять з елементами гри у футбол зумовлений низкою причин: інтересом дітей та батьків до занять цим видом оздоровчо-рекреаційної рухової активності, забезпеченням можливості емоційного, творчого самовираження, нервово-психічної розрядки, отримання дітьми задоволення від занять, формування рухової культури: культури тіла, культури рухів, культури тілесного здоров'я, розумної організації дозвілля, розваги, комунікативної компетентності в рамках неформального спілкування, самовдосконалення, ведення здорового способу життя. The paper deals with studying the innovative approaches to the organization of recreational activities for preschoolers on the premises of sports and health-enhancing clubs. The results of the survey established that the parents have a positive attitude and highly appraise the innovative approaches to the organization of health-enhancing and recreational activities on the premises of club associations. Children’s football clubs are especially attractive among preschool age children. Attractiveness of activities with the elements of football is due to a number of reasons: the interest of children and parents in this type of health-enhancing and recreational physical activity, opportunities provided for emotional and creative self-expression, neuropsychic relaxation, pleasure derived by children from the classes, and development of physical culture: corporeal culture, cultures of movements, culture of body health, rational organization of leisure, entertainment, communicative competence in the framework of informal communication, self-improvement, and healthy lifestyle.
Innovative Approaches to the Organization of Health-Improving and Recreational Activities for Children of Preschool Age
Keywords: діти дошкільного віку; рекреаційні заняття; інновації; спортивно-оздоровчі клуби; рухова активність; preschool age children; recreational activities; innovations; sports and health-enhancing clubs; physical activity